The effects of aerobic exercise training at two different intensities in obesity and type 2 diabetes: Implications for oxidative stress, low-grade inflammation and nitric oxide production - Krause, M.; Rodrigues-Krause, J.; O'Hagan, C.; Medlow, P.; Davison, G.; Susta, D.; Boreham, C.; Newsholme, Philip; O'Donnell, M.; Murphy, C.; De Vito, G. (Springer-Verlag, 2014)
Aims: To investigate the effect of 16 weeks of aerobic training performed at two different intensities on nitric oxide (tNOx) availability and iNOS/nNOS expression, oxidative stress (OS) and inflammation in obese humans with or without type 2 diabetes mellitus (T2DM). Methods: Twenty-five sedentary, obese (BMI > 30 kg/m2) males (52.8 ± 7.2 years); 12 controls versus 13 T2DM were randomly allocated to four groups that exercised for 30 min, three times per week either at low (Fat-Max; 30–40 % VO2max) or moderate (T vent; 55–65 % VO2max) intensity. Before and after training, blood and muscle samples (v. lateralis) were collected. Results: Baseline erythrocyte glutathione was lower (21.8 ± 2.8 vs. 32.7 ± 4.4 nmol/ml) and plasma protein oxidative damage and IL-6 were higher in T2DM (141.7 ± 52.1 vs. 75.5 ± 41.6 nmol/ml). Plasma catalase increased in T2DM after T vent training (from 0.98 ± 0.22 to 1.96 ± 0.3 nmol/min/ml). T2DM groups demonstrated evidence of oxidative damage in response to training (elevated protein carbonyls). Baseline serum tNOx were higher in controls than T2DM (18.68 ± 2.78 vs. 12.34 ± 3.56 μmol/l). Training at T vent increased muscle nNOS and tNOx in the control group only. Pre-training muscle nNOS was higher in controls than in T2DMs, while the opposite was found for iNOS. No differences were found after training for plasma inflammatory markers. Conclusion: Exercise training did not change body composition or aerobic fitness, but improved OS markers, especially when performed at T vent. Non-diabetics responded to T vent training by increasing muscle nNOS expression and tNOx levels in skeletal muscle while these parameters did not change in T2DM, perhaps due to higher insulin resistance (unchanged after intervention).